Prospects for Ukraine in Regionalization and Globalization Processes - S. Sardak; S. Radziyevska (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper focuses on the state of Ukraine's participation in regionalization and globalization processes. The main goal of Ukraine's participation in regionalization and globalization processes is to obtain status of a full member of the EU, which becomes topical in connection with the signing of the association agreement with the EU and the adoption of the export strategy to increase Ukrainian exports of goods while improving its commodity structure. The system approach, the comparative analysis are used, the international statistical data and the materials of the Ukrainian state statistics services are processed. Directions for expanding integration ties are suggested. Priority markets are determined for the export of goods of Ukraine to countries of the EU, Asia, America and Africa.